Correlation of Soluble Programmed Death Ligand-1 (sPD-L1) with Alpha-Fetoprotein Levels as a Predictor of Prognosis in Hepatocellular Carcinoma Patients - Chaerunisah, Sari; Suyata; Mgs M. Irsan Saleh (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Hepatocellular carcinoma (HCC) is the most common primary liver malignancy and one of the leading causes of cancer death worldwide. Chronic hepatitis B virus infection is the most common etiology of HCC. Programmed death ligand-1 (PD-L1) is a protein that is overexpressed on the surface of tumor cells, which can be detected in serum (sPD-L1). Elevated sPD-L1 concentrations in the plasma of cancer patients are associated with poor prognosis in HCC patients, as indicated by increased AFP levels. There have been no previous studies examining the correlation of sPD-L1 levels with AFP in HCC patients. The aim of the study was to determine the correlation of sPD-L1 and AFP as predictors of prognosis in HCC patients. Methods: The research is an observational study with a cross-sectional design to see the correlation of sPD-L 1 with serum alpha-fetoprotein levels in HCC patients at Dr. Mohammad Hoesin General Hospital Palembang starts from April to July 2023. Measurement of sPD-L1 levels and serum AFP levels is carried out using ELISA examination. Results: Of the 28 subjects studied, HCC patients were more commonly found in men (89.29%) aged 18-60 years (75%). sPD-L1 and AFP values were found to be increased in the advanced stages of HCC. The sPD-L1 value is directly proportional to the serum AFP value. Conclusion: There is a strong positive correlation between sPD-L1 levels and serum AFP levels caused by hepatitis B in HCC patients, so the higher the sPD-L1, the higher the serum AFP levels.